Factors Influencing Local Communities’ Intention to Support Sustainable Tourism Development in the Lake Toba Super-Priority Destination - Pohan, Muhammad Yasir Arafat; Putri, Nadhila Nastiti; Arjuna, Syukron (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of local residents’ perceptions of economic, sociocultural, and environmental impacts on their support for sustainable tourism development in Lake Toba, one of Indonesia’s super-priority destinations. A quantitative approach was employed, with data collected through questionnaires distributed to local communities around the Toba Caldera. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that all three factors—economic, sociocultural, and environmental impacts, significantly affect residents’ support, with sociocultural impact emerging as the most dominant factor. These results confirm the relevance of Social Exchange Theory, indicating that community support increases when perceived economic, social, and environmental benefits outweigh potential costs. The study provides policy implications suggesting that sustainable tourism development should adopt a holistic approach that balances economic opportunities, environmental preservation, and the strengthening of local cultural identity.